2018
DOI: 10.1111/cbdd.13311
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhibitor of the new antibiotic resistance protein OptrA

Abstract: The antibiotic resistance (ARE) subfamily of ABC (ATP-binding cassette) proteins confers resistance to a variety of clinically important ribosome-targeting antibiotics and plays an important role in infections caused by pathogenic bacteria. However, inhibitors of ARE proteins have rarely been reported. Here, OptrA, a new member of the ARE proteins, was used to study inhibitors of these types of proteins. We first confirmed that destroying the catalytic activity of OptrA could restore the sensitivity of host ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Such EQ2 variants have been successfully employed to trap other ABCF proteins on the ribosome because they allow binding but prevent hydrolysis of ATP (Chen et al, 2014;Crowe-McAuliffe et al, 2018;Crowe-McAuliffe et al, 2021;Kasari et al, 2019). The OptrA-EQ2 variant was earlier shown to have a compromised in vitro ATPase activity and be incompetent in promoting antibotic resistance in vivo (Zhong et al, 2018). Affinity purification via the FLAG3 tag was performed in the presence of 0.5 mM ATP from clarified lysates prepared from the E. faecalis DlsaA strain expressing the FLAG3-tagged ARE-ABCF, either wildtype or EQ2-variant.…”
Section: Cryo-em Structures Of Poxta-70s Complexesmentioning
confidence: 99%
“…Such EQ2 variants have been successfully employed to trap other ABCF proteins on the ribosome because they allow binding but prevent hydrolysis of ATP (Chen et al, 2014;Crowe-McAuliffe et al, 2018;Crowe-McAuliffe et al, 2021;Kasari et al, 2019). The OptrA-EQ2 variant was earlier shown to have a compromised in vitro ATPase activity and be incompetent in promoting antibotic resistance in vivo (Zhong et al, 2018). Affinity purification via the FLAG3 tag was performed in the presence of 0.5 mM ATP from clarified lysates prepared from the E. faecalis DlsaA strain expressing the FLAG3-tagged ARE-ABCF, either wildtype or EQ2-variant.…”
Section: Cryo-em Structures Of Poxta-70s Complexesmentioning
confidence: 99%
“…Nevertheless, a possible approach could be small fragment library screening followed by elucidation of ligand‐bound ARE ABC‐F structure and modification of ligand to outcompete the natural substrate, such as ATP, for disabling the catalytically important conserved signature motif and Walker B following glutamate residues. Recently, a novel inhibitor of OptrA that targets its ATPase center was discovered . Through saturation transfer difference experiments, homology modeling of OptrA, docking, and molecular dynamics, the authors have proposed the binding site interactions of their inhibitor lead for structural optimization beyond its reported 30% ATPase activity suppression.…”
Section: Implications For Drug Designmentioning
confidence: 99%
“…10,11 The optrA, found in 2015, was reported for its ATP hydrolysis activity to be associated with linezolid resistance. 12 Also, previous study reported that there were different amino acid substitutions in optrA. 13 In this study, we investigated the molecular characterization of optrApositive enterococci and explored the function of varied types of optrA on the linezolid susceptibility.…”
Section: Introductionmentioning
confidence: 99%